With the clouds of heaven : the book of Daniel in biblical theology - Hamilton, James M., 1974- (Downers Grove : InterVarsity press, 2014)
"Perceiving within evangelical studies that lack of a robust canonical biblical-theological treatment of the book of Daniel, James Hamilton explores how it contributes to the Bible's unfolding redemptive-historical storyline. By setting Daniel in the broader context of biblical theology, this study helps move us towards a clearer understanding of how we should live today in response to its message"--Back cover.
Includes bibliographical references (pages 237-246) and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Criticism, interpretation, etc